2021
DOI: 10.1038/s41598-021-83331-9
|View full text |Cite
|
Sign up to set email alerts
|

Reproducing asymmetrical spine shape fluctuations in a model of actin dynamics predicts self-organized criticality

Abstract: Dendritic spines change their size and shape spontaneously, but the function of this remains unclear. Here, we address this in a biophysical model of spine fluctuations, which reproduces experimentally measured spine fluctuations. For this, we characterize size- and shape fluctuations from confocal microscopy image sequences using autoregressive models and a new set of shape descriptors derived from circular statistics. Using the biophysical model, we extrapolate into longer temporal intervals and find the pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…The motor walking in the system may not be sufficiently slow to yield SOC behavior, which requires a sharp separation of time scales between slow driving and fast dissipation, and the nonconservative transfer of mechanical energy between network components may also play a role ( 13 , 24 , 46 , 67 , 68 ). We note, however, that recent studies have indicated that branched cytoskeletal networks polymerizing against a flexible membrane can produce shape fluctuations of the membrane that exhibit true SOC, leaving open the question of whether criticality is an inherent feature of cytoskeletal dynamics ( 69 , 70 ).…”
Section: Discussionmentioning
confidence: 92%
“…The motor walking in the system may not be sufficiently slow to yield SOC behavior, which requires a sharp separation of time scales between slow driving and fast dissipation, and the nonconservative transfer of mechanical energy between network components may also play a role ( 13 , 24 , 46 , 67 , 68 ). We note, however, that recent studies have indicated that branched cytoskeletal networks polymerizing against a flexible membrane can produce shape fluctuations of the membrane that exhibit true SOC, leaving open the question of whether criticality is an inherent feature of cytoskeletal dynamics ( 69 , 70 ).…”
Section: Discussionmentioning
confidence: 92%
“…New models were proposed to investigate these spontaneous spine shape fluctuations [106,107] and their implications in LTP [14, 107] by continuously changing the membrane according to the actin dynamics. These models couple the biochemical and mechanical properties of dendritic spines, and thus, their function and structure.…”
Section: Models Incorporating Spine Shapementioning
confidence: 99%
“…AMPARs dynamics also span from seconds, in studies of AMPARs lateral diffusion [85], to minutes, when investigating different sources of AMPARs [15,98]. Moreover, models investigating spontaneous fluctuations of spine shape [106,107] or AMPARs [89] can span from seconds to minutes, respectively (figure 2).…”
Section: Design Considerations For Model Buildingmentioning
confidence: 99%
See 1 more Smart Citation
“…Models linking these findings to single spine dynamics using various approaches already exist 12 , 15 , 22 , 30 , 31 . In this study, we introduce a model that can reproduce both long-term potentiation (LTP)-triggered spine changes and activity-independent spine fluctuations within a common framework.…”
Section: Introductionmentioning
confidence: 99%